Cost-effectiveness analysis of CDK4/6 inhibitors in the second-line treatment for HR+/HER2− advanced or metastatic breast cancer - Wang, Kaixuan; Liu, Shixian; Li, Shunping; Gao, Jie (Frontiers in Pharmacology, 2025)
ObjectiveThe aim of this study was to compare the cost-effectiveness of various CDK4/6 inhibitors plus fulvestrant with fulvestrant monotherapy in the second-line treatment for patients with HR+/HER2− advanced or metastatic breast cancer from the Chinese healthcare system perspective.MethodsA partitioned survival model was established to investigate the total costs, quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratio (ICER) over a 10-year lifetime horizon. Clinical data was derived from the MONARCH 2 trial, PALOMA 3 trial and MONALEESA 3 trial; direct medical costs and utilities were acquired from local charges and published literature. Scenario, one-way and probabilistic sensitivity analyses were performed to test the robustness of the model.ResultsIn the base-case analysis, abemaciclib plus fulvestrant, palbociclib plus fulvestrant, ribociclib plus fulvestrant resulted in ICERs of $3,636.51/QALY, $1,256.32/QALY, and $39,654.78/QALY, respectively, compared with fulvestrant monotherapy. In the pairwise comparison between three CDK4/6 inhibitors, abemaciclib plus fulvestrant was the most cost-effectiveness treatment option. One-way sensitivity analysis showed that the proportion of subsequent treatment, utility values of progression-free survival (PFS), cost of best supportive care had a significant impact on ICER. Probabilistic sensitivity analysis demonstrated that abemaciclib plus fulvestrant achieved an overwhelming superiority with a 99.82% probability to be the most cost-effective strategy in China at the current price and willingness-to-pay threshold.ConclusionFrom the perspective of Chinese healthcare system, abemaciclib plus fulvestrant represented the optimal regimen as the second-line treatment for HR+/HER2− advanced or metastatic breast cancer.